Use of Circulating Tumor DNA in Prognostic Analysis of Patients with Solid Malignant Tumors of the Gastrointestinal Tract: Systematic Review - Abreu, Gabriel dos Santos Martins de (2025)
Introduction: The circulating tumor DNA (ctDNA), one of the main exponents of liquid biopsy, constitutes a promising tool in the field of oncology. However, its use in clinical practice, despite being varied, requires further support. Objective: To evaluate the impact of using circulating tumor DNA as a tool to qualify the prognosis of patients with solid malignant tumors of the gastrointestinal tract. Method: Systematic review based on cohort studies, using the MEDLINE, LILACS, SciELO, Science Direct and BASE databases. The assessment of methodological quality was carried out by the Newcastle-Ottawa Quality Assessment Scale. Results: Of the 557 articles initially found, the final sample of the present study included 13 articles. Higher rates of tumor recurrence and lower survival rates were observed in ctDNA-positive patients with tumors from all main sites of the gastrointestinal tract, compared to those who were ctDNA-negative. This correlation was consistent across all tumor stages. Furthermore, ctDNA proved to be more effective in predicting tumor recurrence proven by radiological examination when compared to carcinoembryonic antigen, typically used in this context. Conclusion: The results found support the use of circulating tumor DNA in the described scenario, in a complementary way to the prognostic assessment tools commonly used in current clinical practice.